Control de un robot seguidor de línea tipo diferencial mediante visión artificial. - Chanco Alvear, Jorge Luis (2018)
With the impulse of the artificial vision techniques applied to the control of robotic prototypes, the need arose to understand, learn, test and develop algorithms that allow control of the navigation of line-following robots. In the present work we opted for the implementation of a test robot prototype, for the testing and validation of artificial vision algorithms for the students of the robotics club of the Salesian Polytechnic University headquarters Quito campus south. Based on studies of the different software packages available for the development of artificial vision applications and by analyzing the technical characteristics of the different embedded systems, it was determined that the Raspberry Pi card is suitable to house the artificial vision algorithms applied to the case study. Through the implementation of the robotic prototype together with the artificial vision algorithm, its effectiveness was evaluated by means of field tests, for which tracks with different degrees of difficulty were designed, in which it resulted in an effectiveness of 90% with trajectories that have curves greater than 10 cm radius and angles greater than 90 degrees.